Effectiveness of Regional Development Planning: A Systematic Literature Review - Ilham Akbar; Saiman Saiman; Salahudin Salahudin (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
This study aims to analyze the effectiveness of regional development planning through various planning models. This study used the literature study method by reviewing articles in previous studies obtained through the Scopus web and processed with the VOSviewer application. Based on the results of this study, several topics were found that have strong ties to regional development planning, namely decision making, decision support, land use, stakeholders, and coordination. The results obtained from the previous study show the main key in regional development planning was to make good use of the existing land, that is why careful planning for sustainable development was obtained. The limitations of this study were related to the source of the data obtained, where the articles reviewed are only sourced from the Scopus data base so this study does not have data that can be compared. Therefore, further research was expected to use a comparative analysis approach involving the Scopus database and the Web of Science (WoS).